How to write a scientific paper - Ljiljana Vučković-Dekić (Биомедицинска истраживања, 2014)
The results of a research must be communicated to as large an audience as possible, and the best way to achieve this goal is to publish a paper in scientific journal. The scientific paper has strong structure and organization, the main chapters following the IMRAD acronym, which stands for Introduction: , Material: and Methods: , Results: and Discussion: , but other sections are important, as well. This paper deals with each of specific sections of a manuscript, enlightening us as about both technical and ethical aspects of scientific writing.
Keywords: scientific paper; scientific writing; publishing ethics